Selection Strategy and Steps for the Preparation of Arabic Teaching Materials - Sofia Hafar Raihanun Febrian; Rosadi Rosadi; Dinda Hasnah Haliza; Nayla Tiara Latifa Al Haq; Muhamad Maulana Yusup; Muhammad Ali Firdaus (UIN Sunan Gunung Djati Bandung, 2026)
The availability of Arabic teaching materials has a very important role in achieving learning goals. The success of the learning process depends on the integration between teachers, students, and teaching materials. This research aims to understand the method of selection and also the preparation of good Arabic teaching materials. This research uses the library research method with a qualitative approach to analyze in depth the selection strategy and the steps for the preparation of effective and efficient Arabic teaching materials. The results of the study explain that the method of selecting and preparing Arabic teaching materials must be carried out systematically, relevantly, and adjusted to the needs of students and the curriculum so that it can increase the effectiveness of learning, although in its implementation there are still various challenges that require a flexible, creative, and evaluative teacher approach so that the learning process runs optimally.